2022
DOI: 10.1136/bmjopen-2021-055918
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a prehospital-stage prediction tool for traumatic brain injury: a multicentre retrospective cohort study in Korea

Abstract: ObjectivesPredicting diagnosis and prognosis of traumatic brain injury (TBI) at the prehospital stage is challenging; however, using comprehensive prehospital information and machine learning may improve the performance of the predictive model. We developed and tested predictive models for TBI that use machine learning algorithms using information that can be obtained in the prehospital stage.DesignThis was a multicentre retrospective study.Setting and participantsThis study was conducted at three tertiary aca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…Choi et al provided a novel ML model, named elastic net (EN), to predict the TBI outcomes. This study showed that EN would be a promising model in the future30 . Although the e ciency of ML models has been developed case by case till today, it is not yet precisely clear how accurate the predictions made by AI can be and how much we can rely on them.…”
mentioning
confidence: 61%
See 1 more Smart Citation
“…Choi et al provided a novel ML model, named elastic net (EN), to predict the TBI outcomes. This study showed that EN would be a promising model in the future30 . Although the e ciency of ML models has been developed case by case till today, it is not yet precisely clear how accurate the predictions made by AI can be and how much we can rely on them.…”
mentioning
confidence: 61%
“…In 2022, Choi et al 30 developed new models to predict the diagnosis and prognosis of TBI patients at the prehospital stage. This multi-center retrospective study included 1169 TBI cases that were admitted from 2014 to 2018 in different hospitals in Korea.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In 2022, Choi et al 25 developed new models to predict the diagnosis and prognosis of TBI patients at the prehospital stage. This multi-center retrospective study included 1169 TBI cases that were admitted from 2014 to 2018 in different hospitals in Korea.…”
Section: Literature Reviewmentioning
confidence: 99%